Ẓawāhir al-Insyā’ at-Ṭalabiy Wa Ma’ānīhi al-Balāghiyyah Fī ar-Riwāyah at-Tārīkhiyyah “al-Andalusiy al-Akhīr” Li Ahmad Amin - As-Sa'idah, Rahmah; Nasiruddin, Nasiruddin; Ismail, Muhammad (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2024)
Objective- Insya Thalabi is a word or sentence that has nothing to do with honesty or lies. The purpose of this study is to find out the sentences of Insya Thalabi in the historical novel